Efektivitas Limbah Rambut dalam Menurunkan Kadar Minyak Oli pada Air Limbah Bengkel - Zainal Akhmadi; Suharno Suharno (Poltekkes Kemenkes Pontianak, 2017)
Abstract: Effectiveness Of Hair Waste In Reducing Waste Oil Level In Waste Water Of Service Station. Waste service stations classified as B3 waste because they contain hazardous materials that may damage or pollute the environment or endanger human health. Â The purpose is to determine the efficient design of wastewater treatment with the combination of hair waste as media capture and coconut shell charcoal as filtration media in reducing total oil in wastewater. This study is quasi-experimental. The independent variables include combinations of hair waste as media capture and coconut shell charcoal as filtration media with a thickness of 40 cm and 80 cm, while the dependent variable is the oil content in the wastewater. The location of research is motor vehicle repair shop Tire MTL jl. Wahid Hasyim, office Surya Pratama numbers 4-5 Pontianak. The content of the oil content of wastewater motor vehicle repair shop before treatment by an average of 26.466 mg / l and 4.283 mg / l of after treatment. From the results of these measurements that effectively amounted to 83.6%. Waste Water Treatment with a combination of hair waste and coconut shell charcoal as an effective filtration media for reduced total oil in wastewater for the motor vehicle repair shop.Abstrak: Efektivitas Limbah Rambut Dalam Menurunkan Kadar Minyak Oli Pada Air Limbah Bengkel. Limbah bengkel digolongkan sebagai limbah B3 karena mengandung bahan berbahaya yang dapat merusak atau mencemari lingkungan atau membahayakan kesehatan manusia. Tujuan penelitian adalah menentukan desain efektivitas pengolahan air limbah dengan kombinasi limbah rambut capture media dan arang tempurung kelapa sebagai media filtrasi dalam mengurangi minyak total dalam air limbah. Penelitian ini merupakan kuasi-eksperimental. Variabel bebas mencakup kombinasi dari limbah rambut capture media dan arang tempurung kelapa sebagai media filtrasi dengan ketebalan 40 cm dan 80 cm, sedangkan variabel dependen adalah kandungan minyak dalam air limbah. Lokasi penelitian adalah kendaraan bermotor bengkel ban MTL Jl. Wahid Hasyim, Kantor Surya Pratama Nomor 4-5 Pontianak. Isi kandungan minyak dari air limbah kendaraan bermotor bengkel sebelum pengobatan dengan rata-rata 26,466 mg / l dan 4,283 mg / l dari setelah perawatan. Dari hasil pengukuran ini yang efektifitas sebesar 83,6%. Limbah Pengolahan Air dengan kombinasi limbah rambut dan arang tempurung kelapa sebagai media filtrasi efektif total minyak berkurang dalam air limbah untuk kendaraan bermotor bengkel.